First Description of Natural and Experimental Conjugation between Mycobacteria Mediated by a Linear Plasmid - Rabello, Michelle Christiane da Silva; Matsumoto, Cristianne Kayoko; de Almeida, Luiz Gonzaga Paula; Menendez, Maria Carmen; de Oliveira, Rosangela Siqueira; Silva, Rosa Maria; Garcia, Maria Jesus; Leão, Sylvia Cardoso (PLOS ONE, 2012)
Background In a previous study, we detected the presence of a Mycobacterium avium species-specific insertion sequence, IS1245, in Mycobacterium kansasii. Both species were isolated from a mixed M. avium-M. kansasii bone marrow culture from an HIV-positive patient. The transfer mechanism of this insertion sequence to M. kansasii was investigated here. Methodology/Principal Findings A linear plasmid (pMA100) was identified in all colonies isolated from the M. avium-M. kansasii mixed culture carrying the IS1245 element. The linearity of pMA100 was confirmed. Other analyses suggested that pMA100 contained a covalently bound protein in the terminal regions, a characteristic of invertron linear replicons. Partial sequencing of pMA100 showed that it bears one intact copy of IS1245 inserted in a region rich in transposase-related sequences. These types of sequences have been described in other linear mycobacterial plasmids. Mating experiments were performed to confirm that pMA100 could be transferred in vitro from M. avium to M. kansasii. pMA100 was transferred by in vitro conjugation not only to the M. kansasii strain from the mixed culture, but also to two other unrelated M. kansasii clinical isolates, as well as to Mycobacterium bovis BCG Moreau. Conclusions/Significance Horizontal gene transfer (HGT) is one of most important mechanisms leading to the evolution and diversity of bacteria. This work provides evidence for the first time on the natural occurrence of HGT between different species of mycobacteria. Gene transfer, mediated by a novel conjugative plasmid, was detected and experimentally reproduced.